Investigation of Photovoltaic Assisted Misting System Application for Arbor Refreshment - Esen, Hikmet; Tuna, Omer (Hindawi Ltd, 2015)
In this study, for the first time in the literature, solar assisted cooler with misting system established on an arbor with an area of 24m(2) and georeferenced in Elazig (38.6775 degrees N, 39.1707 degrees E), Turkey, is presented. Here, we present a system that reduces interior temperature of the arbor while increasing humidity. Also, the system generates required electricity with a solar photovoltaic module to power pressurized water pump through an inverter and stores it in a battery for use when there is no sunlight. The model of the photovoltaic module was implemented using a Matlab program. As a result of being an uncomplicated system, return on investment for the system is 3.7 years.
Keywords: Performance; Roof